2020
DOI: 10.14218/erhm.2020.00001
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Lipopolysaccharides and Risk of Advanced Colorectal Adenoma

Abstract: Background and objectives: Production of lipopolysaccharides (LPS) from the outer membrane of Gram-negative bacteria promotes the survival of cancer cells. Systemic level of LPS is considered a biomarker for microbial translocation. The association between LPS and the risk of colorectal tumors is not well known. The goal of this study was to examine the association between LPS serum levels and risk of advanced colorectal adenoma (ACA). Methods: In this colonoscopy clinic-based case-control study, cases were ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Of great importance, besides Irinotecan, we demonstrated that this probiotic could also protect against the membrane damage provoked by LPS-induced inflammation, LPS excess being a prevalent trait of dysbiosis, chronic gut inflammation, and colon cancer [ 40 , 41 , 42 ]. To address this point, a Caco-2/dU937 co-culture model of intestinal inflammation was treated with LPS, thus provoking FITC-dextran flux across the Caco-2 monolayer.…”
Section: Discussionmentioning
confidence: 99%
“…Of great importance, besides Irinotecan, we demonstrated that this probiotic could also protect against the membrane damage provoked by LPS-induced inflammation, LPS excess being a prevalent trait of dysbiosis, chronic gut inflammation, and colon cancer [ 40 , 41 , 42 ]. To address this point, a Caco-2/dU937 co-culture model of intestinal inflammation was treated with LPS, thus provoking FITC-dextran flux across the Caco-2 monolayer.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Chen et al 7 investigated the association between LPS serum levels and risk of ACA.In that colonoscopy clinic-based study, male patients with diagnosis of ACA and polyp-free control individuals were phenotyped for comparative analyses with age, ethnicity, and information on demographics, lifestyle, and medical history along with serum levels of LPS measurement.Examining the LPS levels based on the characteristics and substratification of adenoma, the investigators showed that patients with largesized adenoma (>2 cm), villous adenoma, or high-grade dysplasia tended to have higher serum levels of LPS compared to patients with smaller, tubular adenoma, and adenoma without high-grade dysplasia, respectively. Although LPS levels were slightly higher in patients with ACA compared to controls, the subtle differences in the LPS levels did not reach statistical significance.…”
Section: Is There An Association Of Circulatory Lps and Risk Of Advanmentioning
confidence: 99%